Peningkatan Literasi Dasar Anak Usia Dini Melalui Media Kartu Kata Bergambar di TK Perwari 1 Tasikmalaya - Nurisma, Indi; Nugraha, Dadan; Azhar Yamin, Alfian (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
This study was motivated by the low basic literacy skills of early childhood learners in recognizing letters, letter sounds, reading, and writing their own names. The purpose of this research was to improve the basic literacy skills of children aged five to six years through the use of illustrated word card media. The research employed a Classroom Action Research approach based on the Kemmis and McTaggart model, conducted in two cycles. The subjects were fifteen Group B children from Perwari 1 Kindergarten in Tasikmalaya City. Data were collected using observation, field notes, and documentation techniques. The data types included both qualitative and quantitative data. Data were analyzed using descriptive qualitative techniques and quantitative calculations involving average scores and percentage achievements. The findings showed a significant improvement in children’s basic literacy skills. In the pre-cycle stage, the average achievement was 35.71%, increasing to 70% in the first cycle, and reaching 91.42% in the second cycle. This improvement indicates that the use of illustrated word cards successfully captured children's attention and stimulated their learning interest in recognizing and understanding letters and words in an enjoyable way. It is concluded that illustrated word cards are effective interactive visual media for enhancing early childhood literacy skills